1991
DOI: 10.1007/bf00184707
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the influence of cyproterone acetate on the sonographic image of the benign prostate in patients treated with local hyperthermia

Abstract: A total of 114 patients suffering from prostatic symptoms due to benign hyperplasia (BPH) and scheduled for surgery elected to participate in a clinical trial of local hyperthermia therapy to the prostate. One group was given cyproterone acetate (CPA) as well. Transrectal ultrasound (TRUS) was performed before and following such treatment. Interesting changes in the volume and the configuration of the gland were observed. Prostatic volume measured 1 month following chemotherapy showed a 20°70 reduction in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…However, in the present study no correlation was noted between the changes observed on echography and the clinical outcome at 1 month of follow-up [2]. A longer follow-up period may well alter this finding.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in the present study no correlation was noted between the changes observed on echography and the clinical outcome at 1 month of follow-up [2]. A longer follow-up period may well alter this finding.…”
Section: Discussioncontrasting
confidence: 54%